Tutors' and Tutees' Behaviors, Attitudes, and Perspectives Regarding EFL Peer Tutoring in Higher Education in Mexico - Janeth Sanchez-Aguilar (Universidad Nacional de Colombia, 2021)
This article reports on the findings of a mixed methods research study on tutors' and tutees' behaviors and attitudes during the tutoring sessions and their perceptions about English language peer tutoring at a bilingual, international, and sustainable university in central Mexico. Observation, peer assessment, and semistructured interviews results suggest that tutees and tutors asked and answered questions and had a positive attitude towards error correction in almost all the sessions. Likewise, they reveal that participants clarified doubts, seemed motivated, motivated their peers, and had a constructive attitude towards teaching and learning from a peer most of the time during the tutoring. Furthermore, results indicate that the participants were positive about the experience, the sessions, their peers, and the influence in their learning.